Dysregulated lipid metabolism in late preterm low birth weight neonates: A case-control study on maternal lipid levels and early metabolic programming implications - Jing Liu; Lijuan Tang; Qi Sun; Di Lv; Yuanmei Chen; Fang Ye; Die Liu; Qin Hui; Haixiao Liang; Chao Wang; Qi Zhang (PeerJ)
Objectives While low birth weight (LBW) is a recognized risk factor for adult metabolic syndrome, the unique lipid metabolic phenotype of late preterm low birth weight (LPTB-LBW) neonates—who experience dual exposures to shortened gestation and intrauterine growth restriction—remains uncharacterized. This study specifically examines whether the convergence of prematurity and growth restriction synergistically disrupts lipid metabolic programming. Methods Using ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS), we compared lipidomic profiles of 88 plasma samples: 45 LPTB-LBW (340/7-366/7 weeks, <2,500 g) and 43 later preterm birth-normal birth weight (LPTB-NBW, 340/7-366/7 weeks, 2,500–4,000 g) controls. Multivariate orthogonal partial least squares-discriminant analysis and univariate modeling identified discriminant lipids. Maternal-neonatal lipid continuity was assessed through Spearman’s correlation analysis. Result A total of 1,173 lipids were identified, categorized into five major lipid classes, with 349 significantly different lipids detected (324 upregulated and 25 downregulated) in the LPTB-LBW group. All glycerolipids were upregulated, accounting for 50% (162/324) of the upregulated lipids. Long-chain polyunsaturated triglycerides (TG) showed extreme elevations, such as TG (18:2_18:3_18:4) and TG (18:2_20:4_20:5). Monoglycerides, including MG (18:2) and MG (18:1), were also significantly elevated. Among glycerophospholipids (GP), 76 species were upregulated, with notable increases in phosphatidylethanolamines such as PE (O-18:0_22:3) and PE (18:2_22:1), while PG (20:4_22:6) was significantly reduced. All differentially expressed ceramides, including Cer (d26:3/33:1(2OH)), Cer (d29:2/30:2(2OH)), and Cer (d28:3/31:1(2OH)), were upregulated, whereas sphingosines were downregulated. Cholesterol esters were decreased, while bile acids, free fatty acids and acylcarnitines were elevated. KEGG pathway enrichment analysis highlighted significant perturbations in cholesterol, glycerolipid, and sphingolipid metabolism. Maternal high-density lipoprotein cholesterol (HDLC) levels during early pregnancy showed exclusive negative correlations with neonatal lipids, particularly triacylglycerol TG (16:0_18:2_18:2) (r =  − 0.33, p = 0.002), diacylglycerols, and ceramides, whereas no associations were observed for maternal low density lipoprotein (LDLC), TC, or TG. Conclusions LPTB-LBW neonates exhibit a unique lipidomic phenotype marked by hyperaccumulation of glycerolipids (e.g., long-chain polyunsaturated TGs), elevated ceramides, and altered phospholipid species (increased PE, decreased PG). Maternal HDLC levels negatively correlated with specific neonatal lipids. These findings highlight early-life lipid alterations in LPTB-LBW infants and the need for further investigation into their clinical implications.